Timing of HPV vaccination as adjuvant treatment of CIN2+ recurrence in women undergoing surgical excision: a meta-analysis and meta-regression - Petráš, Marek; Dvořák, Vladimír; Lomozová, Danuše; Máčalík, Roman; Neradová, Sylva; Dlouhý, Pavel; Malinová, Jana; Rosina, Jozef; Lesná, Ivana Králová (Sexually transmitted infections, 2023)
OBJECTIVE: The main aim was to determine the overall vaccine effectiveness (VE) against recurrent cervical intraepithelial neoplasia grade 2 or worse (CIN2+) including specific VE associated with timing of human papillomavirus (HPV) vaccination using data from published studies. DESIGN: Meta-analysis and meta-regression. DATA SOURCES: A computerised literature search was undertaken using the MEDLINE, EMBASE, International Pharmaceutical Abstracts, Derwent Drug File, ProQuest Science and Technology, Cochrane and MedRxiv databases. To be eligible, the studies, with no language restrictions, had to be published between 1 January 2001 and 25 May 2023. REVIEW METHODS: Included were studies with an unvaccinated reference group that assessed CIN2+ recurrence irrespective of the HPV genotype in women undergoing conisation provided. The present study was carried out in compliance with the Preferred Reporting Items for Systematic Review and Meta-Analyses and Meta-analysis Of Observational Studies in Epidemiology guidelines. The risk of study bias was assessed using the Newcastle-Ottawa Quality Assessment Scale. The Grading of Recommendations Assessment, Development, and Evaluation guidelines were used to assess the strength of evidence for the primary outcome. Data synthesis was conducted using meta-analysis and meta-regression. RESULTS: Out of a total of 14 322 publications, 20 studies with a total of 21 estimates were included. The overall VE against recurrent CIN2+ irrespective of the HPV genotype achieved 69.5% (95% CI: 54.7% to 79.5%). While the HPV vaccine valency, follow-up duration, type of study including its risk of bias had no effect on VE, the highest VE of 78.1% (95% CI: 68.7% to 84.7%) was reported for women receiving their first dose not earlier than the day of excision. This outcome was supported by additional analyses and a VE prediction interval ranging from 67.1% to 85.4%. CONCLUSIONS: The outcome of this meta-analysis and meta-regression convincingly showed the beneficial effect of post-excisional HPV vaccination against CIN2+ recurrence. Studies published to date have been unable to determine whether or not vaccination, completed or initiated before conisation, would be associated with more favourable results. PROSPERO REGISTRATION NUMBER: CRD42022353530.
Keywords: infekce papilomavirem; dysplazie děložního hrdla; Papillomavirus Infections; vakcíny proti papilomavirům; ženské pohlaví; Uterine Cervical Neoplasms; Vaccination; Humans; vakcinace; human papillomavirus; Papillomavirus Vaccines; Female; nádory děložního čípku; Uterine Cervical Dysplasia; genital neoplasms, female; lidé; vaccination